The Effect Of Financial Performance, Institutional Ownership, And Intellectual Capital On Firm Value, With Corporate Social Responsibility Disclosure As Moderating Variable - Widodo, Setya Hadi; Asyik, Nur Fadjrih; Mildawati, Titik (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
Agriculture was important in the national economy, society's survival, food suppliers, and food and work suppliers. This study examined and analyzed financial performance, institutional ownership, and intellectual capital on firm value, with Corporate Social Responsibility Disclosure as a moderating ng variable at Agricultural sector companies. The population comprised IDX agricultural sector companies for three years (2018-2020). Furthermore, the study was quantitative. The data collection technique used purposive sampling. In line with that, there were 22 samples with 66 observations. Moreover, the data analysis technique used multiple linear regression with Moderate Regression Analysis (MRA) and SPSS 26. As a result, the final performance positively affected the firm's value. Likewise, institutional ownership positively affected the firm's value. However, intellectual capital did not affect the firm's value. Additionally, Corporate Social Responsibility could not moderate the relationship between financial performance and firm value. Similarly, Corporate Social Responsibility could not moderate the relationship between Institutional Ownership and firm value. Likely, corporate social responsibility could not moderate the relationship between intellectual capital and firm value.